2015
DOI: 10.1002/2015gl064576
|View full text |Cite
|
Sign up to set email alerts
|

Deep and shallow sources for the Lusi mud eruption revealed by surface deformation

Abstract: The Lusi mud eruption, in East Java, Indonesia, began in May 2006 and continues to the present. Previous analyses of surface deformation data suggested an exponential decay of the pressure in the mud source but did not constrain the location, geometry, and evolution of the possible source(s) of the erupting mud and fluids. To map the surface deformation, we employ multitemporal interferometric synthetic aperture radar and analyze a well‐populated L‐band data set acquired by the Advanced Land Observing Satellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Surface modeling deformation recorded by InSAR (Shirzaei et al, ) recently confirmed that Lusi is fed by two distinct regions located at approximately 1.5 km and >4 km depth. These regions correspond to two fluid sources that were distinguished by geochemical analysis (Mazzini et al, , , ).…”
Section: Geological Setting and Lusi Plumbing Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface modeling deformation recorded by InSAR (Shirzaei et al, ) recently confirmed that Lusi is fed by two distinct regions located at approximately 1.5 km and >4 km depth. These regions correspond to two fluid sources that were distinguished by geochemical analysis (Mazzini et al, , , ).…”
Section: Geological Setting and Lusi Plumbing Systemmentioning
confidence: 99%
“…The eruption site reached flow rates of up to 180.000 m 3 /d (Mazzini et al, ) and currently (February 2017) in the order of 80.000 m 3 /d. Lusi is a unique system on Earth due to its longevity and has been studied extensively over the past decade with geological investigations (Davies et al, ; Istadi et al, ; Mazzini et al, ; Sawolo et al, ; Tanikawa et al, ; Tingay et al, ), geochemical and experimental approaches (Mazzini et al, , ; Vanderkluysen et al, ), geophysical methods (Karyono et al, ; Manga et al, ; Mauri, Husein, Mazzini, Irawan, et al, ; Mauri, Husein, Mazzini, Karyono, et al, ; Obermann et al, ; Shirzaei et al, ), and numerical studies (Collignon et al, ; Lupi et al, ; Lupi et al, ; Mazzini et al, ; Rudolph et al, ; Sohrabi et al, ; Svensen et al, ). However, despite the numerous studies, several questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…On 9 September, the second borehole started to erupt a diluted mud similar to that erupted at the first crater, perhaps owing to lateral expansion of mobilized mud [Rudolph et al, 2011;Shirzaei et al, 2015], although there is no evidence to support this hypothesis. The total gas flux remained almost the same but was Geophysical Research Letters 10.1002/2015GL064571 partitioned between the two craters.…”
Section: Geological Setting and Chronology Of Fiumicino Eventmentioning
confidence: 99%
“…Geertsma () uses nuclei theory to show that total volume change observed at the Earth's surface is 2(1 − υ ) times the volume change in a subsurface reservoir, which is consistent to more recent results (Walsh, ). The expression of total volume change beneath the surface based on InSAR observation is given by Shirzaei et al (). Assuming monotonic surface deformation, the only meaningful solutions are those of which volume changes are pervasively positive or negative (De Natale & Pingue, ).…”
Section: Methodsmentioning
confidence: 99%